Optimization of Zakat Management for People's Welfare (Case Study at the Amil Zakat Board in Yogyakarta Special Region) - Nindya Ayu Zulkarnain; Nunung Nurlaela (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2019)
This study aims to analyze the optimization of zakat at the Yogyakarta Special Region Amil Zakat Agency (BAZNAS DIY) based on how the BAZNAS DIY strategy in maximizing the management of zakat potential and how the effectiveness of distributing zakat in BAZNAS DIY in helping the welfare of the people. This research is descriptive qualitative. The data of this research are primary data and secondary data sourced from BAZNAS DIY. The results of this study indicate, BAZNAS strategy in maximizing zakat management, namely zakat publication strategy, for example, socialization on zakat management, public counseling, disciplining NPWZ cards (Zakat Obligatory Tax Number), Optimizing the collection and distribution of zakat in DIY can be influenced by three important factors namely zakat potential owned by the community, the amount of potential zakat funds absorbed by BAZNAS DIY, and the success of the distribution, but whether or not successful in the collection of zakat and utilization of zakat is carried out only by zakat management institutions. The results of this study are expected to be a reference and increase awareness of the community to pay zakat on BAZNAS DIY for the income they receive.